(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Emotion is an integral part of Holocaust education and inculcating empathy in learners is a well-used pedagogical tool to encourage learners to connect with the victims. This is necessary because of the vast number of victims who died at the hands of the Nazis and their collaborators – six million Jews and five million non-Jews. These numbers are generally difficult to comprehend and there can be a tendency to crush thoughts of all the victims together into a single unit, say, the six million, rather than embrace the thought of six million individuals. To help learners relate better to the Jewish victims and survivors, the personal stories of individuals are often told to personalise the Holocaust. This is a tool used in both schools and museums by history teachers and museum educators. Teaching the Holocaust is not a dispassionate, disconnected experience for history teachers. They are often personally affected whether to a greater or lesser degree, and both their teaching and understanding of the Holocaust are often linked to their personal stories. This article is based on the story of one history teacher, whose personal story shaped her Holocaust pedagogy and philosophy when she taught about the Holocaust. The Holocaust is included in the national history curriculum for Grade 9 and 11 learners in the South African school curriculum. Within a qualitative, narrative inquiry framework, the article discusses the personal story of Florence, a Coloured South African history teacher. Along with her family, she did not personally experience apartheid trauma, as many other current South African history teachers did, nor did her family have any personal connections to World War II Europe. Florence simply drew on her personal experiences as a young girl growing up in a lower middle-class family to formulate her own pedagogy with which to teach the Holocaust and engender empathy in her learners. She did this by including techniques such as visualisations to create a certain mood in the classroom before embarking on teaching what, to her, was a horrific, evil event, and to ensure that the learners did not take what they were going to hear lightly. Her methodology was devised to inculcate empathy and enhance depth of understanding.